2016
DOI: 10.1016/j.celrep.2016.04.075
|View full text |Cite
|
Sign up to set email alerts
|

The Size of Activating and Inhibitory Killer Ig-like Receptor Nanoclusters Is Controlled by the Transmembrane Sequence and Affects Signaling

Abstract: SummarySuper-resolution microscopy has revealed that immune cell receptors are organized in nanoscale clusters at cell surfaces and immune synapses. However, mechanisms and functions for this nanoscale organization remain unclear. Here, we used super-resolution microscopy to compare the surface organization of paired killer Ig-like receptors (KIR), KIR2DL1 and KIR2DS1, on human primary natural killer cells and cell lines. Activating KIR2DS1 assembled in clusters two-fold larger than its inhibitory counterpart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 50 publications
6
75
0
Order By: Relevance
“…Further, phosphorylated KIR molecules are not distributed uniformly; rather, they are localized in discrete microclusters within the larger KIR cluster at the inhibitory synapses . In a recent study with super‐resolution microscopy, it is seen that KIR organizes into nanoclusters, and that SHP‐1 preferentially associates with larger KIR nanoclusters . The implication of such distribution of phosphorylated KIR at inhibitory synapses is not understood.…”
Section: Inhibition Of Nk Cell Cytotoxicitymentioning
confidence: 99%
“…Further, phosphorylated KIR molecules are not distributed uniformly; rather, they are localized in discrete microclusters within the larger KIR cluster at the inhibitory synapses . In a recent study with super‐resolution microscopy, it is seen that KIR organizes into nanoclusters, and that SHP‐1 preferentially associates with larger KIR nanoclusters . The implication of such distribution of phosphorylated KIR at inhibitory synapses is not understood.…”
Section: Inhibition Of Nk Cell Cytotoxicitymentioning
confidence: 99%
“…A single dimorphism in the transmembrane region determines the signalling capacity; allotypes with R245 transduce a functional inhibitory signal and those with C245 have reduced inhibitory signalling 112. Super‐resolution microscopy has revealed that the nanoscale organization of KIR at cell surfaces depends on the transmembrane sequence, which in turn affects downstream signalling 113. Further modifying the functional range of KIR2DL1 are polymorphisms in the extracellular and cytoplasmic domains that regulate avidity and specificity, as well as the level of cell‐surface expression (Fig.…”
Section: Kir Ligand Bindingmentioning
confidence: 99%
“…The signaling cascade will only be triggered if there is a true interaction. The degree of receptor/ligand clustering might also influence the down-stream signaling, as shown by Oszmiana et al (80). Therefore, the reporter cells may be a more physiological system compared to Fc proteins or tetramers.…”
Section: Discussionmentioning
confidence: 93%